A Low-Cost and Low-Density Cement Slurry System Suitable for a Shallow Unconsolidated Stratum. (11th June 2020) - Yue, Jiaping; Liu, Zhaonian; Wang, Jie; Sun, Ting; Wu, Zhiqiang; Geng, Yanan
Abstract : The shallow unconsolidated stratum in the offshore oilfield is characterized by large porosity, low temperature, and weak formation and often faces problems such as low density and poor compressive strength of a cement slurry, among others, which pose serious challenges to construction. A high-performance low-density cement slurry system must be used for cementing to ensure the safety of subsequent drilling and mining on-site and to reduce the cost of cement slurry for the efficient development of oil and gas fields. Based on these problems, according to the principle of particle gradation, a mixture with a high accumulation rate and low density composed of five types of mineral materials, i.e., artificial microbeads, floating beads, microsilicon, fly ash, and slag, has been developed through a large number of indoor experiments, and a set of low-cost and low-density cement slurry systems has been developed; these systems are suitable for the shallow loose formations of offshore oil fields. The cement slurry system meets the requirements of the cementing operation conducted under different temperatures and pressures. The density range is 1.4–1.7 g/cm 3, which can be adjusted. The cement slurry is stable and exhibits good fluidity. The thickening time meets the requirements of cementing construction. Moreover, the compressive strength of the cement paste is high, and the compressive strength of cement paste is greater than 12 MPa for 24 h and 14 MPa for 48 h of curing at 50°C, which maximizes the economic benefits. The research results provide technical support for the safe and efficient development of offshore oil and gas fields.